A Practitioner’s Guide to Spousal Support in Divorce Proceedings - Payne, Julien (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1988)
The objective of this paper is to alert Bench and Bar to the cutting edge of tomorrow’s arguments in Family Law. The dichotomy between law in theory and law in action is underlined, and practical hints are offered to lawyers concerning the proper management of a family law file.Substantive legal issues are also addressed with specific regard to current controversies concerning spousal support orders under the Divorce Act, 1985, (S.C. 1986, c. 4). The popular notion that this Act introduced only cosmetic changes is challenged and the significance of the rulings of the Supreme Court of Canada in Pelech, Richardson and Caron is addressed in some detail. Particular attention is paid to the effect of prior agreements on spousal and child support claims under the new Divorce Act.The conduct of the parties is viewed from a realistic as well as a doctrinal perspective and the role of fixed term spousal support orders is briefly analysed.The blending of theory and practice should prove that there is much to be said for the proposition that “each case depends on its own facts” and one of these facts is the philosophical approach of the particular judge to marriage, divorce and ongoing spousal support after the judicial termination of marriage.